Pengaruh penggunaan wayground terhadap civic participation siswa SMP kelas VIII - Nazwa Albana Gusmi Zain; Winarno; Muhammad Hendri Nuryadi (Journal of Education, Cultural and Politics, 2026)
This study examines the effect of using wayground learning media on civic participation of eighth grade junior high school students. This is motivated by the problem of student activity which is a form of civic participation in the form of student participation in asking questions, expressing opinions, and collaborating with friends. This study uses a quasi-experimental quantitative method that tests the existence of causes and effects as well as the level of relationship between causes and effects by giving predetermined treatments to several control groups and experimental groups for comparison. This study is supported by the constructivism theory developed by Piaget. The results of this study obtained an Asymp. Sig. (2-tailed) value in the experimental class of 0.001 where if looking at the criteria, the results are less than 0.05 (<0.05) which means H0 is rejected and H1 is accepted, so it can be concluded that the effect of using wayground learning media on students' civic participation in the material of preserving my nation's culture with a study on eighth grade students at SMP Negeri 1 Polokarto is proven.